2023
DOI: 10.7759/cureus.35914
|View full text |Cite
|
Sign up to set email alerts
|

Oval Root Canals Prepared With Two Different Endodontic Rotary Files: An In Vitro Study Comparing the Incidence of Dental Defects

Abstract: Objective: This study aims to investigate and compare the establishment of dentinal cracks during root canal preparation using a stereomicroscope and a scanning electron microscope (SEM). Materials and methods: Sixty removed human mandibular premolars were separated into three groups of 20: two experimental and one control. Within the randomized controlled experimental groups, root canals were constructed. Group I: the Waldent walflex file and Group II: the Trunatomy (TRN) file. Group III: the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…According to prior research, every technique that was tested in the study resulted in dentin cracks. 11,13 In this investigation, the experimental groups' dentin was discovered to have cracks, whereas the control group's did not. Consequently, the null hypothesis is not possible.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…According to prior research, every technique that was tested in the study resulted in dentin cracks. 11,13 In this investigation, the experimental groups' dentin was discovered to have cracks, whereas the control group's did not. Consequently, the null hypothesis is not possible.…”
Section: Discussionmentioning
confidence: 77%
“…The apical region must be properly cleaned and shaped because it is crucial for instrumentation. 11 The geometry of the cross section, designs, heat treatments, file movement can all lead to cracks in NiTi files. Waldent Walflex files, which come from Waldent, India, are triangular-cross sectioned rotary files with sharp cutting edges that are incredibly flexible and less prone to wear out with frequent use.…”
Section: Introductionmentioning
confidence: 99%
“…Dentinal cracks can occur when the tensile stress on the root canal wall exceeds the tensile strength of the dentin [ 8 ]. These microcracks could propagate under masticatory load, during retreatment, post space preparation, or insertion, and get converted to complete cracks leading to vertical root fractures, often demanding tooth extraction [ 4 ]. Kim et al [ 9 ] uncovered a potential link between the design characteristics of NiTi rotary instruments and the frequency of vertical root fractures and concluded that the traits of rotary file design have an impact on the amount of apical stress and strain concentration created during root canal preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Human dentin is viscoelastic, and during biomechanical preparation, instruments contact the root canal wall and apply forces that lead to a temporary stress concentration on the dentin. This may result in minor cracks, which can progress into vertical root fractures during obturation, post-placement, and retreatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%